THE INTERACTION OF ISLAM AND LOCAL CULTURES: A STUDY OF ISLAMIC PRACTICES IN SOUTHEAST ASIA - Wijaya Wijaya; Wella Ayu Apriliani; Li Na (Journal of Noesantara Islamic Studies, 2026)
Islam in Southeast Asia has developed through continuous engagement with diverse local cultures, producing distinctive religious expressions that reflect both doctrinal continuity and contextual adaptation. Debates surrounding orthodoxy, reform, and cultural legitimacy have intensified in recent decades, highlighting the need for a systematic examination of how Islamic practices are negotiated within plural socio-cultural settings. This study aims to analyze the patterns of interaction between Islamic teachings and local traditions in selected Southeast Asian communities and to identify the mechanisms through which accommodation, contestation, and reinterpretation occur. A multi-site comparative design was employed, integrating quantitative surveys (N = 54), semi-structured interviews, participant observation, and document analysis across Indonesia, Malaysia, and southern Thailand. Inferential statistical tests and thematic coding were used to examine institutional, generational, and interpretive variations. The findings reveal a dominant pattern of contextualized orthodoxy in which local customs are selectively integrated through scriptural reasoning and institutional mediation. Significant differences were identified between traditionalist and reform-oriented groups, indicating the influence of educational affiliation and global religious networks. The study concludes that Islamic practice in Southeast Asia represents a dynamic process of negotiated continuity rather than binary opposition between religion and culture.